ANALISIS PENGARUH REKRUTMEN DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KOMPETENSI PADA PT. ALBEA RIGID PACKAGING SURABAYA - Handini, Dea Galuh (Jurnal Manajerial Bisnis, 2023)
This study aims to examine and analyze the effect of recruitment and job placement on employee performance through competence at PT. Albea Rigid Packaging Surabaya. The unit of analysis in this study were all employees of PT. Albea Rigid Packaging Surabaya, totaling 120 respondents. Samples were taken using a saturated or census sampling technique. Data analysis was performed using statistics with SPSS 22.00 software. Based on the results of validity and reliability, it was found that each variable was declared valid and reliable and had fulfilled the classical assumption test. This study uses the Path Analysis method (path analysis). Based on the results of data analysis using the T test, the results obtained are that recruitment directly has a positive and significant effect on competence; job placement directly has a positive and significant effect on competence; recruitment directly has a positive and significant effect on employee performance; job placement directly has a positive and significant effect on employee performance; competence directly has a positive and significant effect on employee performance; indirect recruitment through competence has a positive and significant effect on employee performance; and work placement indirectly through competence has a positive and significant effect on employee performance at PT. Albea Rigid Packaging Surabaya.